Energy substrate influences the effect of the timing of the first embryonic cleavage on the development of in vitro‐produced porcine embryos in a sex‐related manner. Issue 11 (10th September 2013) - Torner, Eva; Bussalleu, Eva; Briz, Maria D.; Yeste, Marc; Bonet, Sergi
SUMMARY In vitro culture conditions and certain events during the earliest stages of development are linked to embryonic survival, possibly in a sex‐related manner. In vitro‐produced (IVP) porcine embryos cultured with glucose (IVC‐Glu) or pyruvate–lactate (IVC‐PL) were tested for any relationship between the timing of the first embryonic cleavage and development and sex ratio. The embryos were assigned to IVC‐Glu or IVC‐PL groups and classified depending on the timing of their first cleavage: 24, 26, 30, and 48 hr post‐insemination (hpi). They were cultured separately in vitro and evaluated for cleavage rate and pattern, blastocyst rate and stage, cell number, apoptosis, and sex ratio. Regardless of energy source, the percentage of two‐cell stage and fragmented embryos at the time of their first cleavage was, respectively, higher and lower in early‐cleaving embryos. Those embryos cleaved by 24 hpi developed to blastocysts at a higher rate (IVC‐Glu: 37.90 ± 3.06%; IVC‐PL: 38.73 ± 4.08%) than those cleaved between 30 and 48 hpi (IVC‐Glu: 5.87 ± 3.02%; IVC‐PL: 8.41 ± 3.50%). Furthermore, a shift toward males was seen among embryos first cleaved before 30 hpi, versus towards females among those cleaved later. The early‐cleaving embryos, only from the IVC‐PL group, had a higher proportion of expanded blastocysts (81.05 ± 6.54% vs. 13.33 ± 13.33%) with higher cell numbers than their late‐cleaving counterparts. Moreover, a shift toward males only appeared at the blastocyst stage in IVC‐PL embryos. These findings confirm that the timing of the first cleavage influences development of IVP porcine embryos in a sex‐related manner, and it depends on the main energy source of the in vitro culture medium. Mol. Reprod. Dev. 80: 924–935, 2013. © 2013 Wiley Periodicals, Inc.